In Vitro and In Vivo Radiation Sensitization of Human Tumor Cells by a Novel Checkpoint Kinase Inhibitor, AZD7762 - Mitchell, James B. (2010)
PURPOSE: Inhibition of checkpoint kinase 1 (Chk1) has been shown to enhance the cytotoxicity of DNA damaging targeted chemotherapy through cell cycle checkpoint abrogation and impaired DNA damage repair. A novel Chk1/2 inhibitor, AZD7762 was evaluated for potential enhancement of radiosensitivity for human tumor cells in vitro and in vivo xenografts. EXPERIMENTAL DESIGN: Survival of both p53 wild type and mutant human cell lines was evaluated by clonogenic assay. Dose modification factors (DMF) were determined from survival curves (ratio of radiation doses for control versus drug-treated at 10% survival). Flow cytometry, western blot, and radiation-induced tumor regrowth delay assays were conducted. RESULTS: AZD7762 treatment enhanced radiosensitivity of p53 mutated tumor cell lines (DMFs ranging from 1.6–1.7) to a greater extent than for p53 wild type tumor lines (DMFs ranging from 1.1–1.2). AZD7762 treatment alone exhibited little cytotoxicity to any of the cell lines and did not enhance the radiosensitivity of normal human fibroblasts (SF1522). AZD7762 treatment abrogated radiation-induced G2 delay, inhibited radiation damage repair (assessed by γ-H2AX), and suppressed radiation-induced cyclin B expression. HT29 xenografts exposed to 5 daily radiation fractions and 2 daily AZD7762 doses exhibited significant radiation enhancement compared to radiation alone. CONCLUSIONS: AZD7762 effectively enhanced the radiosensitivity of mutated p53 tumor cell lines and HT29 xenografts and was without untoward toxicity when administered alone or in combination with radiation. The results of this study support combining AZD7762 with radiation in clinical trials.